2022
DOI: 10.1021/acsaem.2c02398
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Thiocyanate-Passivated Quasi-Two-Dimensional Dion Jacobson Perovskite Solar Cells for Improved Efficiency and Stability

Abstract: Quasi-two-dimensional (quasi-2D) Dion Jacobson (D-J) layered perovskites have recently emerged as attractive photovoltaic materials due to their out-of-plane charge conduction and superior environmental stability. However, their power conversion efficiency (PCE) still needs to be optimized before these perovskites become competitive with their three-dimensional counterpart. Here, we report D-J phase quasi-2D (XDA)(MA)3(Pb)4(I)13 perovskites processed with an ammonium thiocyanate (NH4SCN) additive, showing a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The pristine 3D perovskite-based device shows a slope of 1.68 k B T / e , which is further reduced to 1.32 k B T / e in the case of 2D/3D perovskite devices. This reduced value of slope n in case of 2D/3D PSCs indicates the suppressed defect-mediated nonradiative recombination owing to the improved film quality and decreased defect density …”
Section: Resultsmentioning
confidence: 95%
“…The pristine 3D perovskite-based device shows a slope of 1.68 k B T / e , which is further reduced to 1.32 k B T / e in the case of 2D/3D perovskite devices. This reduced value of slope n in case of 2D/3D PSCs indicates the suppressed defect-mediated nonradiative recombination owing to the improved film quality and decreased defect density …”
Section: Resultsmentioning
confidence: 95%
“…In order to improve the quality of the DJ perovskite films, researchers have made attempts in manipulating the structures of the spacer cations, the composition of the small A cations, and the deposition methods and the additives. [24][25][26][27][28] In 2017, Kanatzidis et al reported a PCE ≈7% for the first examples of the DJHPSCs using 3-(Aminomethyl)piperidinium (3AMP) as the spacer cation. [11] One year later, authors from the same group improved the crystallinity of the perovskite film by using a mixture of FA and MA cations to construct the DJP film, obtaining a PCE of 12.04%.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the quality of the DJ perovskite films, researchers have made attempts in manipulating the structures of the spacer cations, the composition of the small A cations, and the deposition methods and the additives. [ 24–28 ] In 2017, Kanatzidis et al. reported a PCE ≈7% for the first examples of the DJHPSCs using 3‐(Aminomethyl)piperidinium (3AMP) as the spacer cation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to RP-type spacers, PDA 2+ , possessing a pair of ammonium at both ends of the carbon chain, can link two [MX 6 ] 4À layers within the monolayer through ionic bonds instead of van der Waals bonds. 36,37 Therefore, the connection of two sides of PDA 2+ can be strengthened and the consistency of crystallization improved, resulting in an optimized morphology. At the same time, the characteristic quasi-2D structure is reserved.…”
Section: Introductionmentioning
confidence: 99%